Immune checkpoint inhibitor outcomes and prognostic factors in gynecologic tract melanoma: a single-center analysis - Wang, Jianzhang; Li, Kemin; Li, Rui; Zeng, Jing; Yin, Rutie (Frontiers in Immunology, 2025)
IntroductionGynecologic tract melanoma (GTM) is a rare and aggressive malignancy with limited treatment options and poor prognosis. This study aims to evaluate the outcomes of immune checkpoint inhibitors (ICIs) in patients with GTM and identify prognostic factors influencing survival.MethodsA retrospective analysis was conducted on 45 patients diagnosed with GTM at West China Second University Hospital from January 2019 to September 2024. Data on demographics, clinical characteristics, treatments, and outcomes were collected. Progression-free survival (PFS) and overall survival (OS) were analyzed using Kaplan-Meier curves and Cox proportional-hazards models.ResultsAmong 45 patients, 24 had vaginal melanoma, 18 had vulvar melanoma, and 3 had cervical melanoma. ICIs were administered to 21 patients, but no significant survival benefit was observed. The 1-, 3-, and 5-year survival rates were 87%, 63%, and 31%, respectively. Univariate analysis revealed that patients with a family history of cancer (FHC) and those with lactate dehydrogenase (LDH) levels ≤230 had better PFS. Additionally, FHC, American Joint Committee on Cancer (AJCC) stage I-II, absence of pelvic lymph node metastasis, and LDH levels ≤230 were associated with improved OS. However, in multivariate analysis, only LDH was significantly associated with OS.ConclusionThis single-center study suggests that ICIs have limited efficacy in treating GTM, emphasizing the need for further investigation through larger, multicenter clinical trials. Prognostic factors such as FHC, AJCC stage, lymph node involvement, and LDH levels may aid in risk stratification and personalized treatment planning. However, due to the nature of this study, external cohorts are still needed for validation.